SOCIAL ASSISTANCE POLICY IN INDONESIA: CORRUPTION, POLITICIZATION, AND GOVERNANCE CHALLENGES - M. Umar, Mujiburrahman; Hamidi, Muslem; Jagdish S Joshi; Fauzan Putraga Al Bahri; Rauzi Ramazalena (Jurnal Sosiologi Dialektika Sosial, 2025)
Corruption in social assistance programs in Indonesia represents a critical failure of public policy with far-reaching impacts on societal welfare. This study aims to analyse the relationship between social assistance policies, corrupt practices, and politicization by political actors, while also assessing their implications for governance. Employing a qualitative narrative approach and literature review combined with public policy analysis, the research seeks to understand how social assistance programs function both as instruments of welfare and as political tools. The findings reveal that weak leadership commitment and low institutional integrity have frequently led to the misuse of social assistance as a political instrument ahead of elections, while simultaneously opening space for systematic corruption. A comparative study with China and Rwanda demonstrates that the success of anti-corruption efforts is largely determined by the political will of leaders and the strengthening of governance systems. Therefore, reforming Indonesia’s social assistance policies should be directed toward three key aspects: strengthening anti-corruption regulations, digitizing transparent distribution systems, and ensuring political leadership commitment to uphold integrity. This article underscores that social assistance policies are not merely about welfare distribution, but are also deeply tied to the sustainability of democracy and the legitimacy of governance.